STUDI EKSPLORASI FAKTOR-FAKTOR KESUKSESAN PROYEK KONSTRUKSI DI INDONESIA - Annisa Azhar Firdausi; Toriq arif ghuzdewan; Ashar Saputra; Akhmad Aminullah (Journal of Civil Engineering and Planning (JCEP), 2020)
The high rate of growth of the construction sector in Indonesia has not been matched by its level of success. Problems are still found in many construction projects that result in project unsuccessfulness, including time loss and bad quality work. In order to support the success of construction projects in Indonesia, the aim of this study is to determine the critical factors that influence the success of construction projects in Indonesia. Data collection through questionnaires on 417 respondents who were directly involved in the project. The questionnaire was based on 4 previous studies, measured by a 5-point Likert scale of agreement and consisting of 64 project success variables. The analysis was performed using the Exploratory Factor Analysis (EFA). The results of this study indicate that there are 6 factors that influence the success of construction projects in Indonesia, namely: (1) Factors related to the Project Manager; (2) Factors related to the Contractor; (3) Factors related to Supervisors; (4) factors related to the project; (5) Factors related to Owner; and (6) Factors related to Owner2. Keywords : construction project, project success, critical success factor, EFA